Financial incentives to improve progression through the HIV treatment cascade. Issue 6 (November 2015) - Bassett, Ingrid V.; Wilson, David; Taaffe, Jessica; Freedberg, Kenneth A.
Abstract : Purpose of review: We reviewed recent literature on conditional and unconditional financial incentives for their impact on improving movement through the HIV care cascade and HIV prevention. Recent findings: Concepts from behavioral economics may help improve engagement in HIV care by addressing upstream structural risk factors for HIV, such as poverty, or providing conditional rewards for immediate, measurable outcomes related to HIV care. Incentives have been shown to increase uptake of HIV testing. Yet, few studies to date focus on linkage to care: one large USA-based randomized trial failed to show an effect of incentives; and a smaller trial showed improved linkage to care among drug users, but no difference in virologic suppression. Several small USA-based studies have shown an impact of financial incentives on antiretroviral therapy adherence, but without durability beyond the incentive period. HIV prevention has the most robust evidence for decreasing HIV risk-taking behavior among adolescents and may serve as a model for research on the care cascade. Summary: Financial incentives show promise for improving engagement in HIV testing, care, and prevention. Understanding the durability, scalability, ease of implementation, and cost–effectiveness of these different approaches will be critical for maximizing the impact of incentives in curtailing the HIV epidemic.